PERANCANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA CV ADI PUTRA UTAMA PALEMBANG - Henny Yulsiati; Riska Harti (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2026)
This study aims to design a cash sales accounting information system based on Microsoft Access at CV Adi Putra Utama Palembang. The research is motivated by problems in the existing manual cash sales system, which causes inefficiency in recording, data inaccuracies, and limited sales reporting. The research method employs a descriptive qualitative approach with a case study method. System development is conducted using the Software Development Life Cycle (SDLC) Waterfall model, limited to the requirement analysis and system design stages. The results indicate that the proposed system improves transaction recording efficiency, enhances data accuracy, and produces timely and informative sales reports. However, the system still has limitations in terms of functional scope and system integration. Therefore, further development is required to enhance system capabilities and better support the company’s operational and managerial needs in the future.